Injectable hydrogels for anti‐tumour treatment: a review. Issue 3 (28th October 2020) - He, Huan; Xie, Chaoming; Lu, Xiong
Abstract : Injectable hydrogels have become the material of choice for the treatment of solid tumours based on their advantages in loading anti‐tumour materials. This study reviews the main scientific research achievements on anti‐tumour injectable hydrogels in recent years. The gel‐forming mechanism of anti‐tumour injectable hydrogels was listed, and the advantages and difficulties of each gel‐forming mechanism were summarised. In addition, several current anti‐tumour methods based on injectable hydrogels were discussed, including chemotherapy, hyperthermia‐based therapy, catalytic therapy and immune therapy, as well as the integration of diagnosis and treatment to monitor the progress of cancer treatment. The anti‐tumour mechanism and the advantages and disadvantages of various tumour treatments were analysed. Finally, the future development trend of injectable hydrogels for anti‐tumour therapy was discussed.